Systematic Literature Review: Community Based Correction as an Alternative Criminal Justice System - Arya Shauma Hidayatullah; Kusmiyanti Kusmiyanti (SAINTIS Publishing, 2025)
This Study aims to analyzes the high crime rate problem in Indonesia and its impact on the correctional system, specifically the issues of prison (Lapas) overcrowding and high recidivism rates. Data indicates Lapas overcrowding ranged from 89% to 106.84% between 2019 and 2023, while recidivism rates were between 12% and 16% in the same period. Factors contributing to recidivism include a lack of vocational skills, social stigma, poor prison conditions, and insufficient rehabilitation initiatives. To address these challenges, this article proposes the implementation of Community Based Correction (CBC) as an alternative criminal sanction, supported by Indonesian Criminal Code (KUHP) Number 1 Year 2023, which introduces supervision sentences and social work sentences. This research employs a Systematic Literature Review (SLR) approach with the PRISMA framework to review 17 relevant scholarly articles published between 2020 and 2024 from databases such as Google Scholar, Publish or Perish, and SINTA. Data analysis utilized a Narrative Synthesis technique. The review findings indicate that CBC programs, which include restorative justice, stakeholder collaboration for independence, and community supervision, are proven effective in reducing recidivism rates and facilitating the social reintegration of inmates. However, challenges in CBC implementation persist, including discrepancies between policy and practice, insufficient resources, and suboptimal public acceptance. This study emphasizes the importance of a correctional system focused on rehabilitation and guidance with community involvement to achieve better inmate reintegration and create a safer social environment.